Essays on the role of risk and disaster in agricultural development - Ijaz, Arusha (Kansas State University, 2023)
Disasters and inability to deal with risks can have far-reaching socioeconomic implications on the agricultural sector in developing countries. Agriculture plays a significant role in the economic growth of these countries, providing food security, employment, and income generation for the large rural population. However, the agricultural sector in these countries is highly vulnerable to various risks and disasters, which can have lasting effects on productivity, livelihoods, and overall development. The following essays explore the role of risk and disasters on the agricultural sector in developing countries focusing on technology adoption, credit accessibility, and trade opportunities. In the first study, we investigate how two tools that signal the quality of a product affect willingness-to-pay (WTP) elicitation for a familiar good. Using a novel study design that combines an incentivized WTP elicitation and a randomized controlled trial, we estimate the effects of two common quality signaling tools, a reference price and a warranty contract, on WTP of the product. A reference price signals the value of the product, whereas, a warranty reduces the risk associated with product failures or defects, and provides assurance to consumers about the reliability of a product. We find a positive effect of the reference price and no effect of the warranty on WTP. We also document that previous experience using a product plays an important moderating role. We investigate how credit responses of farmers differ to an idiosyncratic versus covariate shock, and according to the nature of the loss, in the second study. We find that households that experience idiosyncratic shocks in more than one period increase their credit uptake significantly more than households that experience negative shock in a single period using a modern difference-in-differences model. Persistent income or asset shocks damage the household’s productive capacity and resourcefulness, forcing it to borrow from informal lenders. Households increase credit from informal credit markets to overcome times of financial distress, especially when they experience productive labor loss. The third study explores how a natural disaster and a relief effort in the form of a trade concession can impact the production and exports in the agricultural sector. Using synthetic control techniques, and data on cotton exports and production of Pakistan, we construct counterfactuals for Pakistani exports and production to find the impact of 2010 floods and the 2012 unilateral tariff waiver from EU to Pakistan. We do not find significant impacts of the tariff waiver on the production and exports of the disaster-stricken country. Overall, this research aims to deepen our understanding of the challenges faced by farmers, the strategies they employ to manage risks, and the broader implications for agricultural development.
Keywords: Risk; Natural disasters; Credit; Technology adoption; Tariff waivers